Allelic hierarchy of CDH23 mutations causing non-syndromic deafness DFNB12 or Usher syndrome USH1D in compound heterozygotes. Issue 11 (22nd September 2011) - Schultz, Julie M; Bhatti, Rashid; Madeo, Anne C; Turriff, Amy; Muskett, Julie A; Zalewski, Christopher K; King, Kelly A; Ahmed, Zubair M; Riazuddin, Saima; Ahmad, Nazir; Hussain, Zawar; Qasim, Muhammad; et al.
Abstract : Background: Recessive mutant alleles of MYO7A, USH1C, CDH23, and PCDH15 cause non-syndromic deafness or type 1 Usher syndrome (USH1) characterised by deafness, vestibular areflexia, and vision loss due to retinitis pigmentosa. For CDH23, encoding cadherin 23, non-syndromic DFNB12 deafness is associated primarily with missense mutations hypothesised to have residual function. In contrast, homozygous nonsense, frame shift, splice site, and some missense mutations of CDH23, all of which are presumably functional null alleles, cause USH1D. The phenotype of a CDH23 compound heterozygote for a DFNB12 allele in trans configuration to an USH1D allele is not known and cannot be predicted from current understanding of cadherin 23 function in the retina and vestibular labyrinth. Methods and results: To address this issue, this study sought CDH23 compound heterozygotes by sequencing this gene in USH1 probands, and families segregating USH1D or DFNB12. Five non-syndromic deaf individuals were identified with normal retinal and vestibular phenotypes that segregate compound heterozygous mutations of CDH23, where one mutation is a known or predicted USH1 allele. Conclusions: One DFNB12 allele in trans configuration to an USH1D allele of CDH23 preserves vision and balance in deaf individuals, indicating that the DFNB12 allele is phenotypically dominant to an USH1D allele. This finding has implications for genetic counselling and the development of therapies for retinitis pigmentosa in Usher syndrome. Accession numbers: The cDNA and protein Genbank accession numbers for CDH23 and cadherin 23 used in this paper are AY010111.2 and AAG27034.2, respectively.